SOCIOCULTURAL EDUCATION OF STUDENTS OF PHILOLOGICAL DEPARTMENTS OF UNIVERSITIES USING ENGLISH - Mahamadyusupovna, Dadadjanova Feruza (International Journal of Psychosocial Rehabilitation, 2020)
This article was written in order to theoretically substantiate and practically develop methods for the formation of sociocultural competence through English for students of the philological faculty of the university. The following tasks are defined and solved in the article: 1) to identify the relationship of language, culture, social factors, as well as the relationship between language learning, in order to establish and characterize the phenomena that make up the content of sociocultural competence; 2) to consider and characterize the content and structure of sociocultural competence formed by students of the philological faculty; 3) to analyze the features of the formation of sociocultural competence in the selected conditions; 4) to justify the principles of selection of the content of education in order to form sociocultural competence among students of the philological faculty; 5) to develop a structure for the organization of educational material for the formation of sociocultural competence in this contingent of students; 6) create a set of exercises aimed at the formation of sociocultural competence of students of the philological faculty; 7) to experimentally test the developed set of exercises. On the basis of the problem, a training methodology was developed, didactic foundations were determined and conclusions were drawn.